Responses to environmental and socio-economic changes in the Karangwangi traditional agroforestry system, South Cianjur, West Java - JOHAN ISKANDAR; BUDIAWATI SUPANGKAT ISKANDAR; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2016)
Iskandar J, Iskandar BS, Partasasmita R. 2016. Responses to environmental and socio-economic changes in the Karangwangi traditional agroforestry system, South Cianjur, West Java. Biodiversitas 17: 332-341. In the past, the swidden agriculturesystem (huma) was dominant in village frontiers of West Java; including in the Karangwangi Village of Cidaun Sub-district, Cianjur District, West Java Province. Culturally, each Karangwangi household owned a right to cultivate upland rice (huma) by felling mature forest (leuweung). Moreover, the land was planted by upland rice and other annual crops, such as corn, cassava, cucumber, and various beans. After harvesting rice and other annual crops, the land was fallowed and transformed into secondary forest (reuma) through natural succession. Moreover, the mature secondary forest (reuma kolot) could be opened for rice planting again in the following year or fallowed for more than 3-5 years. People will shift to another piece of mature secondary forest for rice planting. Today, because of increasing population, decreasing forests, and increasing market economic penetration, the Karangwangi people have predominantly practiced the swidden farming in the non-forest instead of the forest. The forests had culturally been converted to traditional agroforestry systems, such as mixed-garden (kebon tatangkalan), and homegarden (pekarangan). This paper discusses the process of evolution of the swidden farming and innovatory cultural practice among the Karangwangi community, South Cianjur, West Java, in management of the traditional agroforestry systems which have been dynamically affected by ecological and socio-economic changes. Four parts are presented in this paper. In part one, we account for the Karangwangi people used to practice the swidden farming in the forest when the forest area that was still abundant. In part two, we discuss a focus on process of the evolution of the swidden farming, transformed to the traditional agroforestry systems In part three, we elaborate on some changes of the traditional agroforestry system and responses to environmental changes. In part four, it is summarized and inferred of the paper. Based on this study, it can be inferred that by developing innovatory cultural practice, Karangwangi people of South Cianjur, West Java have tended to success to evolve their swidden farming to new condition of the traditional agroforestry systems in sustainable way, despite population growth, the depletion of the forests, and intensive market economic penetration.